PET imaging of brain macrophages using the peripheral benzodiazepine receptor in a macaque model of neuroAIDS - Venneti, Sriram (American Society for Clinical Investigation, 2004)
HIV infection in humans and simian immunodeficiency virus (SIV) infection in macaques result in encephalitis in approximately one-quarter of infected individuals and is characterized by infiltration of the brain with infected and activated macrophages. 1-(2-chlorphenyl)-N-methyl-N-(1-methylpropyl)-3-isoquinoline-carboxamide (PK11195) is a ligand specific for the peripheral benzodiazepine receptor abundant on macrophages and is expressed in low levels in the noninfected brain. We hypothesized that positron-emission tomography (PET) with the carbon-11–labeled, R-enantiomer form of PK11195 ([(11)C](R)-PK11195) could image brain macrophages and hence the development of encephalitis in vivo. [(11)C](R)-PK11195 binding was assessed in the brain using PET in 11 SIV infected macaques, six of which showed increased binding in vivo. Postmortem examination of the brain in these six macaques demonstrated encephalitis, while macaques that did not show an increase in [(11)C](R)-PK11195 binding did not develop SIV encephalitis. Brain tissue from SIV encephalitic macaques also showed increased [(3)H](R)-PK11195 binding compared with binding in nonencephalitic macaques. Increased PK11195 binding in vivo and in postmortem brain tissue correlated with abundance of macrophages but not astrocytes. Our results suggest that PET [(11)C](R)-PK11195 imaging can detect the presence of macrophages in SIV encephalitis in vivo and may be useful to predict the development of HIV encephalitis and in studies of the pathogenesis and treatment of HIV dementia.